ANALISIS PENERAPAN FUNGSI-FUNGSI MANAJEMEN DALAM MENINGKATKAN EFEKTIVITAS DAN EFISIENSI PENGELOLAAN DANA DESA DI DESA LAWA-LAWA KECAMATAN HILISERANGKAI - Krisman Natal Oris Mendrofa; Delipiter Lase; Yamolala Zega; Maria Magdalena Batee (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the implementation of management functions in improving the effectiveness and efficiency of Village Fund management in Lawa- Lawa Village, Hiliserangkai District, Nias Regency. The research background is based on issues arising in Lawa-Lawa Village, such as low community participation in planning, discrepancies between plans and realization, limited capacity of village officials, and weak monitoring systems. This research employs a qualitative approach with a descriptive method, using data collection techniques including interviews, observations, and documentation, which were then analyzed using the interactive model through the stages of data collection, data reduction, data display, and conclusion drawing. The results show that procedurally, the implementation of the four management functions has been carried out in accordance with regulations, but in substance, weaknesses remain. The conclusion of this study is that the implementation of management functions in Lawa-Lawa Village has made a positive contribution to Village Fund management but has not been fully optimized in enhancing effectiveness and efficiency. The inhibiting factors include low community participation, limited capacity of village officials, and weak monitoring systems. The researcher recommends improving human resource capacity, strengthening community participation mechanisms, and implementing more transparent and accountable internal monitoring systems.